The Cool Club: Two Of a kind - "Katschke, Judy" (Harper Entertainment: New Yark, 2000)
Cool: having it, keeping it, trying not to lose it$1! = (Bwhatever happens! Find out how Mary-Kate and Ashley rise to the challenge in these three super-cool stories.s
Keywords: Sisters Juvenile fiction